Measuring The Evaluation And Clarification Of The Implementation Of The Forming Of Village Regulations In The New Normal Time - Muhammad Amin Ladiku (Universitas Negeri Gorontalo, 2021)
Abstract: This study aims to determine the evaluation and clarification of the implementation of the formation of village regulations in the new normal. The method used in this research is empirical or sociological research methodology. This study uses a qualitative approach and sampling using purposive sampling and using qualitative analysis techniques. The results of this study showthe implementation of the evaluation and clarification process by the regent of boalemo on the formation of village regulations in the New Normal period to date is based on not running effectively in accordance with the regent of boalemo regulation no. 25 of 2015 concerning Procedures for Formulating Village Regulations. Because all evaluation stages should be carried out by the Department of Social Affairs and Village Community Empowerment and the clarification stage should be carried out by the Regent through the Legal Section of the Regional Secretariat to clarify the Draft Village Regulation. However, in its implementation, it is completely submitted to the Social Service. Therefore, the process stages in Boalemo Regency are not in accordance with the rules that have been formed.Keywords: Evaluation; Clarification; Village Regulation Draft